Measurement of ski snow-pressure profiles - Scott, N.; Yoneyama, T.; Kagawa, H.; Osada, K. (Sports Engineering, 2007)
Bulge-disc type pressure sensors of diameter 6 mm were fitted as near as possible to the running edge of a modern carved ski. The pressure signals were sampled at 30 Hz during long turns on snow, synchronously with signals from a geomagnetic compass and a pressure pad in the ski boot. The pressure from the snow was found to be highly variable with a mean value of about 50 kPa and dynamic pressure spikes up to 300 kPa. With the outside leg, the snow contact width in the rear part of the ski was found to be slightly wider, on average, than for the front part, as expected for a carving turn. Correlation within the pressure sensor data showed that the rapid pressure fluctuations were probably not due to bumps or features on the snow; instead they were probably caused by many small-scale collapses of the snow structure as the ski passed.